Wolfpack eaudiobook How to come together, unleash our power, and change the game. - Wambach, Abby (Macmillan Audio, 2019)
"Abby is a relatable revolutionary — with WOLFPACK, she inspires the confidence, leadership and sisterhood we all so desperately need right now." — Amy Schumer This program is read by the author. Based on her inspiring, viral 2018 commencement speech to Barnard College's graduates in New York City, New York Times bestselling author, two-time Olympic gold medalist and FIFA World Cup champion Abby Wambach delivers her empowering rally cry for women to unleash their individual power, unite with their pack, and emerge victorious together. Abby Wambach became a champion because of her incredible talent as a soccer player. She became an icon because of her remarkable wisdom as a leader. As the co-captain of the 2015 Women's World Cup Champion Team, she created a culture not just of excellence, but of honor, commitment, resilience, and sisterhood. She helped transform a group of individual women into one of the most successful, powerful and united Wolfpacks of all time. In her retirement, Abby's ready to do the same for her new team: All Women Everywhere. In WOLFPACK , Abby's message to women is: We have never been Little Red Riding Hood. We Are the Wolves. We must wander off the path and blaze a new one: together. She insists that women must let go of old rules of leadership that neither include or serve them. She's created a new set of Wolfpack rules to help women unleash their individual power, unite with their Wolfpack, and change the landscape of their lives and world: from the family room to the board room to the White House. · Make failure your fuel: Transform failure to wisdom and power. · Lead from the bench: Lead from wherever you are. · Champion each other: Claim each woman's victory as your own. · Demand the effing ball: Don't ask permission: take what you've earned. In Abby's vision, we are not Little Red Riding Hoods, staying on the path because we're told to. We are the wolves , fighting for a better tomorrow for ourselves, our pack, and all the future wolves who will come after us. More praise for WOLFPACK: "WOLFPACK is a must-read for all of us determined to teach our kids there are no limits. It's a manifesto for everyone trying to lead — whether it's a team, a company, a family, or a meaningful life." — Serena Williams "I would follow Abby Wambach into any battlefield. I would follow her not because she is a bold leader (although she is one), but because she leads from BESIDE women, not from AHEAD of us...Abby Wambach is what the next level of women's revolution will look like, and I'm DOWN." — Elizabeth Gilbert, bestselling author of Eat, Pray, Love